PERSEPSI MAHASISWA JURUSAN TADRIS MATEMATIKA FAKULTAS TARBIYAH DAN ILMU KEGURUAN IAIN TULU - Miswanto, Miswanto (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2015)
In accordance with the problems and the objectives set forth in this study is to obtain an overview of the perceptions and factors that support and hinder student study program Mathematics Tadris to utilize the Internet as a learning resource. This study used a survey research design, which is used for exploration purposes. Taking into account the availability of time in the study of this opportunity is centered on the study program is Tadris Mathematics courses. Force long years many studies have been completed in order to obtain a small amount. Samples were taken proportional random sampling. Data collection techniques used in this study was a questionnaire. The data collected will be analyzed descriptively by tabulation and percentages. The study concluded that 1). Student perceptions of student study programs Mathematics Tadris to the internet as a learning resource utilization is a. Internet services provided by the campus is quite adequate and needs to be improved. b. With the use of the Internet, students can analyze, collect, store and evaluate the indormasi that has been earned. 2). The factors that support student study program Mathematics Tadris utilize the Internet as a source of student learning is faster, more complete and more in getting resources. 3). Factors that hinder student study program Mathematics Tadris utilizing the Internet as a learning resource is a. Students need to formulate the problem, identify and determine the source and choose which one to use. b. Students sometimes do not find the information needed.Kata kunci: Persepsi, Internet, Belajar